O ensino de língua portuguesa na proposta curricular de São Paulo: abordagens e perspectivas - Firmino, Luiz Alves (2014)
The theme of this study is the teaching of the Portuguese language in Curriculum Proposal of São Paulo: approaches and perspectives, seeking to understand the extent to which the curriculum in Portuguese of São Paulo presents continuity or rupture in the proposed teaching of the mother language. It falls in line Search History and Description of the Portuguese Postgraduate Studies Program in Portuguese at the Pontifical Catholic University of São Paulo. Thus, we aimed to reflect on the implementation of Curriculum Proposal of São Paulo in the period 2008-2009, their approach to teaching English language and on their achievement in school praxis in order to investigate the relationship between theory and practice, under the postulates of Linguistics Historiography , aiming to further establish an interdisciplinary dialogue with Linguistic Education in teacher practice and see the reflection of this Curriculum Proposal in pedagogical practice declared by teachers in response to the proposed questionnaire. To do so, based on studies of Koerner, Bastos, Palma, Turazza among other researchers, we make explicit the theoretical assumptions underlying the Guidelines and Framework Law number 9394/96 as well as the instrument that guides its operation, currently in force 'guidelines and the National Curriculum Guidelines. Made theoretical considerations, we examined the corpus - the proposed curriculum and interviews with teachers of English that operate under the aegis of this proposal, considering the characterization of Curriculum Proposal of São Paulo and interviews as a primary source of research. The survey results indicate that the teachers interviewed, mostly, are not attuned to the perceived paradigmatic rupture in the proposal in question, featuring, in practice they still adopted, a mismatch between theory and practice, and the proposal in question understood only as teaching-learning materials to equip the Portuguese class